We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
60
2
avatar

1. What is the smallest distance between the origin and a point on the graph of \(y=\dfrac{1}{\sqrt{2}}\left(x^2-3\right)? \)

 

 

Thank you guys for your help in advance!

 

 

Ask only one question per post!    (Melody)

 Jul 21, 2019
edited by Melody  Jul 21, 2019
edited by Melody  Jul 21, 2019
 #1
avatar+22896 
+2

1.
What is the smallest distance between the origin and a point on the graph of \(y=\dfrac{1}{\sqrt{2}}\left(x^2-3\right)?\)

\(\text{Let the distance $=s$} \)

 

\(\begin{array}{|rcll|} \hline s^2 &=& x^2+y^2 \quad &|\quad y=\dfrac{1}{\sqrt{2}}\left(x^2-3\right) \\ s^2 &=& x^2+\left(\dfrac{1}{\sqrt{2}}\left(x^2-3\right)\right)^2 \\ s^2 &=& x^2+\dfrac{1}{2}\left(x^2-3\right)^2 \\ \dfrac{d\ s^2}{dx} &=& 2x_{\text{min}}+\dfrac{2}{2} (x_{\text{min}}^2-3)2x_{\text{min}} \\ &=& 2x_{\text{min}}+\dfrac{2}{2} (x_{\text{min}}^2-3)2x_{\text{min}} \\ &=& 2x_{\text{min}}(1+x_{\text{min}}^2-3) \\ &=& 2x_{\text{min}}(x_{\text{min}}^2-2) \\\\ \dfrac{d\ s^2}{dx} &=& 0 \\ 2x_{\text{min}}(x_{\text{min}}^2-2) &=& 0 \\ x_{\text{min}}^2-2 &=& 0 \\ \mathbf{ x_{\text{min}}^2 } &=& \mathbf{2} \\\\ y_{\text{min}} &=& \dfrac{1}{\sqrt{2}}\left(x_{\text{min}}^2-3\right) \\ y_{\text{min}} &=& \dfrac{1}{\sqrt{2}}\left(2-3\right) \\ \mathbf{ y_{\text{min}} } &=& -\dfrac{1}{\sqrt{2}} \\\\ s_{\text{min}} &=& \sqrt{x_{\text{min}}^2+y_{\text{min}}^2} \\ s_{\text{min}} &=& \sqrt{2+\left(-\dfrac{1}{\sqrt{2}}\right)^2} \\ s_{\text{min}} &=& \sqrt{ 2+ \dfrac{1}{2} } \\ s_{\text{min}} &=& \sqrt{ \dfrac{5}{2} } \\ \mathbf{ s_{\text{min}}} &=& \mathbf{1.58113883008\ldots} \\ \hline \end{array}\)

 

laugh

 Jul 22, 2019
 #2
avatar
+1

Denoting the distance between the origin and the parabola by s,

\(\displaystyle s^{2}=x^{2}+y^{2}=x^{2}+\frac{1}{2}(x^{2}-3)^{2} \\ =x^{2}+\frac{1}{2}(x^{4}-6x^{2}+9) \\ = \frac{1}{2}(2x^{2}+x^{4}-6x^{2}+9) \\ =\frac{1}{2}(x^{4}-4x^{2}+9) \\ =\frac{1}{2}\{(x^{2}-2)^{2}+5\}.\)

 

Since \(\displaystyle (x^{2}-2) \ge0,\)

it follows that the least value of s^2 will be 5/2, in which case the least value of s will be sqrt(5/2) and that that happens when x^2 - 2 = 0,

ie. when x = sqrt(2).

 Jul 22, 2019

18 Online Users

avatar